О некоторых особенностях образования отглагольных существительньх на -нье в старобелорусском языке XVI века - Закарьян, М. (Kalbotyra, 1972)
The article deals with the formation of verbal nouns ending in -ньe and their relationship to underlying verbal stems. For want of space, the author confines herself to determining correlations of the morphemic composition of verbal stems in question and those of the grammatical categories of aspect and voice. Lexico-semantic relationship between derived nouns and underlying verbs is not dealt with.A conclusion is drawn that verbal nouns with the suffix -ньe used in business documents written in Old Byelorussian are still very closely connected with corresponding verbs, for the most part retaining aspectual differentiation.